Screening and identification of microRNAs mediating cartilage endplate degeneration in human intervertebral disks - Jiang, Bei; Bai, Chong; Pan, Jie; Shen, Bin; Li, Lijun (Frontiers in Medicine, 2024)
Obtained the cartilage endplate from patients who underwent interbody fusion surgery at the Department of Spine Surgery, Shanghai East Hospital Affiliated to Tongji University, from January 01, 2020 to January 01, 2023. Total RNA extraction from cartilage endplate tissue. Discover differential genes through NGS, To annotate gene functions, all target genes were aligned against the Kyoto Encyclopedia of Genes (KEGG) and Gene Ontology (GO) database. GO enrichment analysis and KEGG enrichment analysis of target genes were performed using phyper, a function of R. The P-value was corrected using the Bonferroni method , and a corrected P-value ≤ 0.05 was taken as a threshold. GO terms or KEGG terms fulfilling this condition were defined as significantly enriched terms. The screened miRNAs and their target protein were verified in vitro by qPCR and WB.RNA was extracted from normal and degenerated cartilage endplate tissues for NGS.Eight down-regulated DEGs and 22 up-regulated DEGs were found. KEGG pathway analysis of these target genes revealed that differential micrornas and target genes were enriched in different signaling pathways, and the regulated signaling pathways were mainly mitochondrial autophagy and autophagy. The qPCR results demonstrated a significant upregulation of miR-25-3p and miR-345-5p in degenerative cartilage endplate tissues (p≤0.001). Western blot analysis revealed that BRD4 exhibited a marked increase in protein expression levels in degenerative cartilage endplate tissues (p≤0.0001), while BECN1 showed a significant decrease in protein expression levels within these samples (p≤0.0001).